Synthesis and cytotoxic evaluation of novel quinazolinone derivatives as potential anticancer agents - Safoora Poorirani; Sedighe Sadeghian-Rizi; Ghadamali Khodarahmi; Marzieh Rahmani Khajouei; Farshid Hassanzadeh (Wolters Kluwer Medknow Publications, 2018)
Nitrogen-rich heterocyclic compounds represent a unique class of chemicals with especial properties and have been modified to design novel pharmaceutically active compounds. In this study, a series of novel quinazolinone derivatives with substituted quinoxalindione were synthesized in two parts. In the first part, 6-(4-amino-3-methylphenoxy)quinoxaline-2,3(1H,4H)-dione was prepared from para-amino -m-crozol in 5 steps. In the next part, 2-alkyl-4H-benzo[d][1,3]oxazin-4-one derivatives were obtained from antranilic acid. Then reaction of 6-(4-amino-3-methylphenoxy)quinoxaline-2,3(1H,4H)-dione with 2-alkyl-4H-benzo[d][1,3]oxazin-4-one derivatives resulted in the production of final componds. The structures of synthesized compounds were confirmed by IR and 1H-NMR. Cytotoxic activity of the compounds were evaluated at 0.1, 1, 10, 50 and 100 μM concentrations against MCF-7 and HeLa cell lines using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) colorimetric assay. Almost all new compounds showed cytotoxic activity in both cell lines. Among tested compounds, 11g displayed the highest cytotoxic activity against both cell lines.